2012
DOI: 10.4209/aaqr.2011.07.0105
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous and Secondary Inorganic Aerosols during Wintertime Fog and Haze over Urban Sites in the Indo-Gangetic Plain

Abstract: The chemical composition of total suspended particulate (TSP) matter and secondary aerosol formation have been studied during wintertime fog and haze events from urban sites (Allahabad and Hisar) in the Indo-Gangetic Plain. The atmospheric abundances of elemental carbon (EC), organic carbon (OC), water-soluble OC (WSOC) suggest that organic matter is a major component of TSP, followed by concentrations of sulphate and nitrate under varying meteorological conditions. The concentrations of EC, OC, and WSOC show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(61 citation statements)
references
References 62 publications
(88 reference statements)
3
57
1
Order By: Relevance
“…Vehicles and fossil fuel emissions are the dominant sources of OC and EC, but have little impact on K + concentrations. In this study, OC was strongly correlated with EC (R 2 = 0.82) during the 2-days period, but the OC/EC ratio (range: 2.8-5.3, mean: 3.4) did not increase, which was significantly lower than those reported for Savannah burning, forest fires, and agricultural waste burning emissions (Andreae, 1983;Park et al, 2005bPark et al, , 2006bReid et al, 2005;Ram and Sarin, 2011;Ram et al, 2012aRam et al, , 2012bZhang et al, 2012b), or slightly lower than that (5.7) from emissions of forest fires in the Indochina (Chuang et al, 2012). Other studies have shown even when biomass materials are burned, a low OC/EC ratio is possible because it depends greatly on the type of materials burned and combustion conditions (Turn et al, 1997;Saarnio et al, 2010;Bae et al, 2012;Zhang et al, 2012a).…”
Section: Characteristics Of Carbonaceous Particlescontrasting
confidence: 45%
“…Vehicles and fossil fuel emissions are the dominant sources of OC and EC, but have little impact on K + concentrations. In this study, OC was strongly correlated with EC (R 2 = 0.82) during the 2-days period, but the OC/EC ratio (range: 2.8-5.3, mean: 3.4) did not increase, which was significantly lower than those reported for Savannah burning, forest fires, and agricultural waste burning emissions (Andreae, 1983;Park et al, 2005bPark et al, , 2006bReid et al, 2005;Ram and Sarin, 2011;Ram et al, 2012aRam et al, , 2012bZhang et al, 2012b), or slightly lower than that (5.7) from emissions of forest fires in the Indochina (Chuang et al, 2012). Other studies have shown even when biomass materials are burned, a low OC/EC ratio is possible because it depends greatly on the type of materials burned and combustion conditions (Turn et al, 1997;Saarnio et al, 2010;Bae et al, 2012;Zhang et al, 2012a).…”
Section: Characteristics Of Carbonaceous Particlescontrasting
confidence: 45%
“…Moreover, the combination of unique weather conditions in this region (long dry season extending from November to May) and geophysical features promotes the accumulation of atmospheric pollution during the non-monsoon season. This leads to the formation of regional scale plumes of air pollutants, known as ABCs, resulting in high concentrations of pollutants on the southern side of the Himalayas (Rengarajan et al, 2007;Ram et al, 2012). Thus, the increase in TSP and PAH concentrations in the non-monsoon season is likely to be due to the combined effects of source strength and accumulation of atmospheric pollutants (Datta et al, 2010).…”
Section: Spatial Distribution and Seasonal Trend Of Tsp And Pah Concementioning
confidence: 99%
“…In addition, the westerly winds during the winter and pre-monsoon seasons create relatively dry and cold conditions. The unique weather conditions of the region (long dry season extending from November to May), combined with its geophysical features create an environment conducive to the accumulation of air pollutants outside the monsoon season, often leading to the formation of air pollutant plumes on a regional scale, called atmospheric brown clouds; this results in high pollutant concentrations on the southern side of the Himalayas (Ram et al, 2012;Rengarajan et al, 2007). Furthermore, the ambient temperature considerably affects the gas-particle partitioning of PAHs (Sitaras et al, 2004;Tham et al, 2008).…”
Section: Seasonal Variations Of Tsp and Pah Concentrationsmentioning
confidence: 99%